Manajemen MUI Tapanuli Utara Dalam Membina Umat Islam di Tengah Penduduk Minoritas Muslim di Tapanuli Utara - Sobirin Ramayanto Tampubolon; Waizul Qarni (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Living as one is the fantasy of all animals on the planet. However, religious people in the North Tapanuli Regency of North Sumatra, as well as other human beings, are subject to social conflict due to a variety of factors. In this manner, there should be a work to make agreement in the existence of strict individuals. The Indonesian Ulema Council of the North Tapanuli Regency in North Sumatra has worked to improve communication between the various religious communities in the North Tapanuli Regency in North Sumatra in order to foster a peaceful and harmonious religious environment. This is why the study titled